Novel AU-rich proximal UTR sequences (APS) enhance CXCL8 synthesis upon the induction of rpS6 phosphorylation - Ang, Zhiwei (PLoS Genet, 2019)
The role of ribosomal protein S6 (rpS6) phosphorylation in mRNA translation remains poorly understood. Here, we reveal a potential role in modulating the translation rate of chemokine (C-X-C motif) ligand 8 (CXCL8 or Interleukin 8, IL8). We observed that more CXCL8 protein was being secreted from less CXCL8 mRNA in primary macrophages and macrophage-like HL-60 cells relative to other cell types. This correlated with an increase in CXCL8 polyribosome association, suggesting an increase in the rate of CXCL8 translation in macrophages. The cell type-specific expression levels were replicated by a CXCL8- UTR-reporter (Nanoluc reporter flanked by the 5’ and 3’ UTR of CXCL8). Mutations of the CXCL8-UTR-reporter revealed that cell type-specific expression required: 1) a 3’ UTR of at least three hundred bases; and 2) an AU base content that exceeds fifty percent in the first hundred bases of the 3’ UTR immediately after the stop codon, which we dub AU-rich proximal UTR sequences (APS). The 5’ UTR of CXCL8 enhanced expression at the protein level and conferred cell type-specific expression when paired with a 3’ UTR. A search for other APS-positive mRNAs uncovered TNF alpha induced protein 6 (TNFAIP6), another mRNA that was translationally upregulated in macrophages. The elevated translation of APS-positive mRNAs in macrophages coincided with elevated rpS6 S235/236 phosphorylation. Both were attenuated by the ERK1/2 signaling inhibitors, U0126 and AZD6244. In A549 cells, rpS6 S235/236 phosphorylation was induced by TAK1, Akt or PKA signaling. This enhanced the translation of the CXCL8-UTR-reporters. Thus, we propose that the induction of rpS6 S235/236 phosphorylation enhances the translation of mRNAs that contain APS motifs, such as CXCL8 and TNFAIP6. This may contribute to the role of macrophages as the primary producer of CXCL8, a cytokine that is essential for immune cell recruitment and activation.